C reactive protein concentrations in neonates: determination by a latex enhanced immunoassay. Issue 9 (September 1984) - O'Callaghan, C; Franklin, P; Elliott, T S; Deverill, I; Richards, N; Powell, R J
Abstract : A latex enhanced immunoassay on a centrifugal fast analyser was used to compare serum C reactive protein concentrations in maternal and neonatal blood. In the neonate the C reactive protein concentration at birth was less than 1.0 mg/l; the concentration rose slightly during the first two weeks of life. There was no correlation between C reactive protein concentrations in maternal and neonatal sera. No significant difference was found between the C reactive protein concentrations in blood obtained by either heel prick or venepuncture.